Valores do trabalho: um estudo entre os profissionais dos Centros de Referência da Assistência Social do Município de Varginha-MG - Aquino, Carla Botrel Consentino De (2015)
Studies of labor values are used as a way to understand the reasons that influence the behavior of professional in daily labor. In this way, if they influence the attitude and the human behavior and guide decisions and interventions in organizational processes (PORTO & TAMAYO, 2008), it is possible to consider its implications, even if indirectly, on the implementation of public policies. Thus emerges the importance of addressing this issue with the professionals of Social Assistance Reference Center - CRAS, a public facility characterized as the gateway to the citizen to Unified System of Social Assistance - SUAS, which was recently established. There by the aim of the research is to understand the values attributed to work by social workers and social advisor of the five unities of CRAS in the city of Varginha-MG, identifying the potentialities and limitations to achieve the CRAS objectives and the implementation of the National Social Assistance Policy. PNAS. The model of work values scale developed by Porto and Tamayo (2003) based on studies by Schwartz (1992) and Ros et al (1999) was used to find the results. The collection and analysis of data were achieved by the application of sociodemographic form and the conduction of a semi-structured interview based on that scale. The results showed the values of Labour Fulfillment and Social Relations as axiological priority of the team and little significance given to the values of Stability and Prestige. In general the team hás values consistent with the objectives of CRAS which can contribute to the implementation of PNAS. Limitations of the study and suggestions for further research are pointed out in the final considerations.